Self-assembling peptide nanostructures on aligned poly(lactide-co-glycolide) nanofibers for the functional regeneration of sciatic nerve. (February 2017) - Nune, Manasa; Subramanian, Anuradha; Krishnan, Uma Maheswari; Kaimal, Suraj Sasidhara; Sethuraman, Swaminathan
Aim: Regeneration of functional peripheral nerve tissue at critical-sized defect requires extracellular matrix analogs impregnated with appropriate biosignals to regulate the cell fate process and subsequent tissue progression. The aim of the study was to develop electrospun aligned nanofibers as architectural analogs integrated with RADA16-I-BMHP1 as biofunctional peptides.Materials & methods: Aligned poly(lactide- co -glycolide) (PLGA)-RADA16-I-BMHP1 nanofibers were fabricated and characterized for their in vitro potential using rat Schwann cell line and in vivo potential using a 10 mm sciatic nerve transection rat model.Results: PLGA-peptide scaffolds significantly promoted higher expression of genotypic markers and bipolar extension of Schwann cells. Further, PLGA-peptide treated animals promoted the native collagen organization, remyelination and showed significantly higher recovery of sensorimotor and motor function than PLGA-treated groups (p < 0.05).Conclusion: Our results demonstrate that self-assembling peptide nanostructures on aligned PLGA nanofibers provided better cell–matrix communication with significant functional restoration of the sciatic nerve.